1998
DOI: 10.1002/(sici)1521-4176(199805)49:5<303::aid-maco303>3.0.co;2-p
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamics, mechanisms and kinetics of metal dusting

Abstract: A survey is given on recent research on “metal dusting” i.e. a catastrophic carburization or rather graphitization of metals and alloys occuring in carbonaceous atmospheres at carbon activities aC>1. The thermodynamics are explained, the mechanisms for iron, low and high alloy steels, nickel and Ni‐base alloys are described and the kinetics derived for iron and low alloy steels. Protection against metal dusting is possible by the presence of sulfur in the atmosphere, since adsorbed sulfur retards carbon transf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
127
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 207 publications
(138 citation statements)
references
References 11 publications
3
127
0
Order By: Relevance
“…7 Chemical modification of the steel surface is also associated with the metal dusting mechanism, which starts as low as 300°C and at a carbon activity greater than the unit. Metal dusting starts when the steel surface is oversaturated with carbon, followed by its disintegration to carbon and metal particles, 8 although the presence of H 2 S seems to inhibit this process. 9 All the above-mentioned mechanisms only offer a partial picture of the mechanism of formation of such a deposit, therefore any proposed solution to prevent or correct petroleum well obstruction problems strongly depends on the characterization of field samples.…”
Section: Introductionmentioning
confidence: 99%
“…7 Chemical modification of the steel surface is also associated with the metal dusting mechanism, which starts as low as 300°C and at a carbon activity greater than the unit. Metal dusting starts when the steel surface is oversaturated with carbon, followed by its disintegration to carbon and metal particles, 8 although the presence of H 2 S seems to inhibit this process. 9 All the above-mentioned mechanisms only offer a partial picture of the mechanism of formation of such a deposit, therefore any proposed solution to prevent or correct petroleum well obstruction problems strongly depends on the characterization of field samples.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of Cr on metal dusting was investigated, the results of which showed that a Cr 2 O 3 layer protected the alloys from metal dusting Grabke 1998). Cr 2 O 3 was observed by Raman spectroscopy on the surface of Alloy 601 tested in our study (see Fig.…”
Section: 3mentioning
confidence: 99%
“…It was suggested that an oxide scale protects alloys, and metal dusting corrosion starts at defects in the oxide scale (Grabke 1998, Grabke et al 1993, 1998. Carbon penetrates through the defects and undermines the oxide scale.…”
Section: 3mentioning
confidence: 99%
“…The most widely accepted theory for Fe-based alloys can be described in the following reaction steps (1-3): (1) rapid transfer of carbon from the gas atmosphere into the iron leading to the growth of a surface cementite layer which acts as a barrier for further carbon transfer; (2) graphite nucleation and deposition, lowering the carbon activity to unity at the Fe 3 C/graphite interface, and initiating cementite decomposition into graphite and iron, which is said to diffuse outwards through the graphite to the graphite-gas interface; and (3) precipitation of iron particles in the coke where they act as catalysts for further graphite deposition. The metal dusting of Ni and Ni-based alloys is considered to follow a similar mechanism to Fe-based alloys, but without forming the metastable intermediate M 3 C. In this case, the nickel atoms have been suggested (4,5) to diffuse via graphite intercalation, and form nano-scale nickel particles which catalyse further carbon deposition.…”
Section: Introductionmentioning
confidence: 99%